2012
DOI: 10.1007/s00429-012-0411-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytoarchitectonical analysis and probabilistic mapping of two extrastriate areas of the human posterior fusiform gyrus

Abstract: The human extrastriate visual cortex comprises numerous functionally defined areas, which are not identified in the widely used cytoarchitectonical map of Brodmann. The ventral part of the extrastriate cortex is particularly devoted to the identification of visual objects, faces and word forms. We analyzed the region immediately antero-lateral to hOc4v in serially sectioned (20 μm) and cell body-stained human brains using a quantitative observer-independent cytoarchitectonical approach to further identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
168
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(178 citation statements)
references
References 115 publications
(178 reference statements)
10
168
0
Order By: Relevance
“…Cortical visual areas were defined by using probabilistic cytoarchitectonic maps. These areas include the OC1/OC2 (occipital cortex) (Amunts et al, 2000), ventral and dorsal OC3 and OC4 (Kujovic et al, 2013;Rottschy et al, 2007), OC5 (Malikovic et al, 2006), and FG1/FG2 (fusiform gyrus) (Caspers et al, 2013). For the probabilistic maps of these regions, we first performed a winner-takes-all algorithm to define unique regions of each area, and then split them into left and right regions.…”
Section: Definition Of Regions Of Interestmentioning
confidence: 99%
“…Cortical visual areas were defined by using probabilistic cytoarchitectonic maps. These areas include the OC1/OC2 (occipital cortex) (Amunts et al, 2000), ventral and dorsal OC3 and OC4 (Kujovic et al, 2013;Rottschy et al, 2007), OC5 (Malikovic et al, 2006), and FG1/FG2 (fusiform gyrus) (Caspers et al, 2013). For the probabilistic maps of these regions, we first performed a winner-takes-all algorithm to define unique regions of each area, and then split them into left and right regions.…”
Section: Definition Of Regions Of Interestmentioning
confidence: 99%
“…First, the variability may simply relate to the microstructural organization (e.g., cytoarchitecture) of the cortex. In the human brain, it has been observed that the size and location of cytoarchitectonic visual areas varies considerably across individuals (Amunts et al, 2000;Caspers et al, 2013;Malikovic et al, 2007;Rottschy et al, 2007;. Because the regional cytoarchitecture is often correlated with the regional specialization of function (Brett et al, 2002;Zilles and Amunts, 2010), the variability of the cytoarchitecture is thus likely a source of the variability in the functional regions.…”
Section: Sources Of Interindividual Variabilitymentioning
confidence: 99%
“…The ventral part of V4 (hOC4v, Rottschy et al, 2007) and the subdivisions of the fusiform gyrus (FG1 and FG2, Caspers et al, 2012) were obtained from recent postmortem cytoarchitectonic atlases (SPM Anatomy Toolbox V2, http://www.fz-juelich.de) and overlapped on the Colin 27 template. These maps were thresholded in order to only show voxels with a probability superior to 50% (above the chance level of being in the given area for a given voxel).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1: A. Color-related areas in the human brain. Cytoarchitectonic areas hOC4v (Rottschy et al, 2007), FG1, FG2 (Caspers et al, 2012), the functionally activated area V8 (Hadjikhani et al, 1998) and the midfusiform color center explored in the right hemisphere of an epileptic patient by Murphey et al (2008). B. Reconstruction of Madame R"s lesion.…”
Section: Methodsmentioning
confidence: 99%